Study on Survival and Sustainable Development of Small- and Medium-Sized Tourism and Hospitality Enterprises in Macao Based on Regional Soft Environment and Competitive Advantage - Cheng, Dongshu; Liu, Kunyuan; Qian, Zichao; Chen, Ziyang; Mao, Honglin (Frontiers in Psychology, 2022)
The small and medium-sized tourism and hospitality enterprises are Macao's main forms of enterprises. This study put forward a new framework of survival and sustainable development from the perspective of competitive advantage and regional soft environment, which significantly holds theoretical and practical research value. The study obtained cross-sectional data of 317 small and medium-sized tourism and hospitality enterprises in Macao through a large-scale questionnaire survey. This paper used exploratory factor analysis and confirmatory factor analysis to test the reliability and validity of each factor system and its measurement scale. The variance analysis is used to judge the differences between the elements. The regression analysis is used to verify the hypothesis of a causal relationship between factors. The structural equation analysis is used to fit the model and make necessary amendments. The results reveal that the government service environment has a significant positive impact on the entrepreneur's ability. In addition, the regional soft environment significantly impacts the competitive advantage of small and medium-sized tourism and hospitality enterprises in Macao. Contrary, the impact of Macao's laws on the acquisition of financial resources and the promotion of entrepreneur ability and innovation ability is found insignificant. In conclusion, the results showed that Macao’s market lacks venture investors where enterprises cannot obtain funds through angel financing or risk financing.